Activity of Hospital Disinfectants against Vegetative Cells and Spores of Clostridioides difficile Embedded in Biofilms - Rashid, Tasnuva (Antimicrob Agents Chemother, 2019)
Clostridioides difficile spores can survive in the environment in either mono- or mixed-species biofilms. However, no previous studies have investigated chemical disinfection of C. difficile spores embedded in biofilms. Thus, the purpose of this study was to assess the in vitro effectiveness of hospital disinfectants against C. difficile spores embedded within biofilms. Five unique C. difficile strains embedded in three different biofilm types grown for 72 or 120 h were exposed to seven different hospital disinfectants. C. difficile abundance [as log(number of CFU/milliliter)] was calculated after manufacturer-determined contact times along with biofilm biomass and microscopy. The primary analysis compared differences between C. difficile vegetative cell and spore counts as well as amounts of biomass after exposure to disinfectants. C. difficile vegetative cells and spores were recovered from biofilms regardless of the type of biofilm growth or biofilm growth time. No disinfectant was able to completely eliminate C. difficile from the biofilms. Overall, Clorox, ortho-phthalaldehyde (OPA), and Virex were most effective at killing C. difficile spores regardless of biofilm age, ribotype, or wash conditions (whether biofilms are washed or unwashed) (P = 0.001, each). Clorox and OPA were also effective at killing total vegetative cell growth (P = 0.001, each), but Virex was found to be ineffective against vegetative cell growth in biofilms (P = 0.77). Clorox and Virex were most effective in reducing biomass, followed by Nixall, OPA, and Vital Oxide. No disinfectant was able to completely eliminate C. difficile embedded within biofilms although differences among disinfectants were noted. Future research will be required to determine methods to eradicate this persister reservoir.